Tüketimde Meşruiyet Sorunu ve Kur’ân - Gül, Ali Riza (Dinî araştırmalar, 2009)
Islam demands legitimacy in the process of consumption as well as in all the human acts. The Islamic principles connected with the consumption are mainly located in the Qur’an. The information contained in various verses show that the consumption legitimacy should start with needs and requests. Because the fact that the needs and demands’ being legitimate require the property, goods and services and the activities of expenditure and exhausting should be in legitimate. It is deemed legitimate in the process of consumption of all kinds of consumer items that are not mentioned as forbidden in the basic sources of Islam, good and clean with respect to the qualities, not cloying, not in the class of invalid as regard to ways of acquiring, prepared religiously in lawful manner. Likewise, all service areas that do not cause great harm to manlike and society or the environment in general are legitimate. The legitimacy in the consumption processes is argued in connection with the current conditions, but in accordance